2019
DOI: 10.1038/s41550-018-0664-0
|View full text |Cite
|
Sign up to set email alerts
|

Detailed polarization measurements of the prompt emission of five gamma-ray bursts

Abstract: Gamma-ray bursts are the strongest explosions in the Universe since the Big Bang, believed to be produced either in forming black holes at the end of massive star evolution [1, 2, 3] or merging of compact objects [4]. Spectral and timing properties of gamma-ray bursts suggest that the observed bright gamma-rays are produced in the most relativistic jets in the Universe [4]; however, the physical properties, especially the structure and magnetic topologies in the jets are still not well known, despite several … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 30 publications
4
80
0
Order By: Relevance
“…We find the BALROG derived location much more precise than that of the standard location analysis (see Fig. 1), allowing us to reduce the systematic errors included in the polarization results presented in Zhang et al (2019). Additionally, it has now been shown that the BALROG locations are systematically more accurate (Berlato et al 2019).…”
Section: Location and Temporal Analysismentioning
confidence: 51%
See 3 more Smart Citations
“…We find the BALROG derived location much more precise than that of the standard location analysis (see Fig. 1), allowing us to reduce the systematic errors included in the polarization results presented in Zhang et al (2019). Additionally, it has now been shown that the BALROG locations are systematically more accurate (Berlato et al 2019).…”
Section: Location and Temporal Analysismentioning
confidence: 51%
“…Using this location, spectral and polarization responses were generated for all data types. We note that a standard GBM position 2 exists and, along with their uncertainties, was used for the polarization results presented in Zhang et al (2019), however, the standard localization technique has known systematics and now possess arbitrarily inflated error distributions (Connaughton et al 2015). We find the BALROG derived location much more precise than that of the standard location analysis (see Fig.…”
Section: Location and Temporal Analysismentioning
confidence: 76%
See 2 more Smart Citations
“…This pipeline can work automatically without manual intervention and will send an email to notify the researchers that new scientific data products have been generated. Up to now, with scientific data products generated by the pipeline of the current version, the in-orbit instrument performance study and calibration have been finished and are presented in Li et al 2018, and the first scientific results of POLAR have been produced and published in Zhang et al 2019 recently. This paper will give a detailed introduction of this pipeline and the main algorithms that are important and specially needed by POLAR.…”
Section: Introductionmentioning
confidence: 99%